Persepsi dan Pengetahuan Masyarakat Desa Basarang Kabupaten Kapuas Terhadap Kebakaran Hutan dan Lahan Gambut - Ardiyansyah Purnama; Mariaty Mariaty; Dagna Dea Diadema (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Forest and peatland fires are significant environmental issues in Central Kalimantan, particularly in Basarang Village, Kapuas Regency. This study aims to analyze community perceptions and knowledge regarding forest and peatland fires to support more effective prevention efforts. A quantitative approach was used, employing survey techniques through questionnaires administered to 30 respondents. The results indicate that the level of public perception is categorized as moderate, with an average score of 65.8%, and the level of knowledge is also moderate, with an average score of 75.0%. The community generally understands the definition, impacts, and regulations related to land fires; however, a gap remains between knowledge and actual practice in the field, such as participation in outreach programs and reporting fire incidents. It was also found that although residents are aware of the dangers of land clearing by burning, some still practice it due to economic constraints and traditional habits. This study recommends enhancing outreach efforts, providing contextual education, and offering tangible government support to strengthen community involvement in sustainable forest and peatland fire prevention.